Apocalypse in Rome : Cola di Rienzo and the politics of the New Age - Musto, Ronald G. (University of California Press, 2003)
On May 20, 1347, Cola di Rienzo overthrew without violence the turbulent rule of Rome's barons and the absentee popes. A young visionary and the best political speaker of his time, Cola promised Rome a return to its former greatness." "A man of modest origins, Cola gained a reputation as a talented professional with an unparalleled knowledge of Rome's classical remains. After earning the respect and friendship of Petrarch and the sponsorship of Pope Clement VI, Cola won the affections and loyalties of all classes of Romans." "At the height of Cola's rule, a conspiracy of pope and barons forced him to flee the city and live for years as a fugitive until he was betrayed and taken to Avignon to stand trial as a heretic. Musto relates the dramatic story of Cola's subsequent exoneration and return to central Italy as an agent of the new pope. But only weeks after he reestablished his government, he was slain by the Romans atop the Capitoline hill.--Publisher description